Pengaruh Penerapan Model PBL Berbantuan Media Video Subtema Keunikan Daerah Tempat Tinggalku - Dewilia Nurvitar Putri; Irvan Permana; Mira Mirawati (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the effect of the PBL model on learning outcomes sub-theme of the uniqueness of the area where I live. This study used a quasi-experimental two-group design approach. The population of this study was the fourth grade students of SDN Batu 08 which consisted of 54 students. The research sample was determined by simple random sampling technique. Samples by SDN Kota Batu 08 class IVA as the experimental group and class IVB as the control group. The data collection method used in this study used the test method, the type of objective in the form of multiple choice. The data collected were analyzed using quantitative descriptive statistical analysis and inferential statistics (t-test). This can be seen from the N-Gain value in the experimental class group of 76, while the control class group got an N-Gain value of 60. The completeness of learning outcomes obtained by the experimental group was 100% while in the control group it was 74%. And the results of hypothesis testing that H0 is rejected and Ha is accepted because tcount (21.2885) > (ttable 2.00665).